Legal issues in Sharī‘ah-compliant home financing in Malaysia: A case study of a Bai Bithaman Ājil contract - Oseni, Umar A.; Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2016)
Purpose – This paper provides a case study on a Sharī‘ah-compliant house loan contract based on the Bai Bithaman Ajil (BBA) contract generally used by Islamic banks in Malaysia. The study emphasises the need to comply with the existing legal framework and execute relevant contracts in line with the Sharī‘ah resolutions of the Sharī‘ah Advisory Council of Bank Negara Malaysia without causing harm (ḍarar) to the customers or introducing uncertain elements or procedures (gharar) in the execution of the agreements. This paper follows the other paper that has been presented elsewhere by the authors (Oseni, Ayob & Abdul Rashid, 2014).